Land Use Change and Soil Quality in The West Slope of Bromo Mountain, East Java, Indonesia - Purnomo Edi Sasongko (Nusantara Science and Technology Proceedings)
Deforestation, intensive cultivation, and mismanagement in Tutur district have caused soil degradation and environmental problems. Soils which develop under secondary forests in west slope of Bromo mountain have been degraded by land-use changes (LUC). The effects of long-term LUC and cultivation were evaluated for six land-use types (LUT) including: 1) secondary forest of natural re-growth (UF), land use changes from forest to 2) vegetables, 3) apple, and 4) Coffee garden with understory plant, 5) Coffee garden without understory plant, and 6). Agro forestry. This study was aim to identify indicators of location specific soil-quality on different land-use types. Soils were sampled from identified cropping system and from forest areas were analyzed soil chemical and physical characteristics. Important soil quality indicators were identified and was developed for the area. Result of the experiment showed that almost all of soil- quality indicators changed significantly to land use changes. Average of soil total nitrogen, Soil organic varbon, pH (H20 and KCl), water aggreagte stability, cation exchange capacity (CEC), clay value were 0.04, -0.77, -0.29, -0.38, -6.49, -9.83, -36.40 respectively. While soil P, silt and sand were increased 16.50, 29.80, and 6.80 respectively. The value of CEC has positive correlation to soil clay and Org-C, and it have negative correlation to silt and sand.